Template-assisted synthesis of ruthenium oxide nanoneedles: electrical and electrochemical properties - Subhramannia, Mahima; Balan, Beena K.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
We here demonstrate the formation of bundles of RuO2 nanoneedles (ca. 100 nm diameter) by a templateassisted electrodeposition from aqueous RuCl3 solution under potentiostatic conditions at room temperature. Cyclic voltammetric measurements in 0.5 M H2SO4 show significantly higher redox-related charging behavior for the RuO2 nanoneedles compared to that of the commercial sample, which is also supported by the electrochemical impedance data. A comparison of the specific capacitance reveals a higher value for nanoneedles (3 F/g instead of 0.4 F/g for the bulk), which has been explained on the basis of enhanced reactivity. More interestingly, electrical transport measurements reveal a transition from metallic to semiconducting behavior especially at low-temperature caused by an impurity scattering mechanism. We anticipate that the present simple route for the fabrication of RuO2 nanostructures will be useful to exploit their potentials in various fields such as electrocatalysis, nanoelectronics, and more importantly for designing supercapacitors.

Carbon nanofiber with selectively decorated pt both on inner and outer walls as an efficient electrocatalyst for fuel cell applications - Balan, Beena K.; Unni, SreeKuttan M.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2009)
A novel electrocatalyst, with excellent Pi dispersion oil the inner and outer wall of a carbon nanofiber (CNF) was prepared by a modified polyol process in which both surface tension and polarity characteristics of the medium were properly adjusted to favor solution entry into the tubular region by capillary filling and homogeneous wetting of the inner wall surface by the solvents. The pristine CNF, which possesses an inherently active inner wall surface and inactive outer Wall surface, led to selective Pt deposition along the inner wall, whereas activation of the outer wall with chemical functionalization resulted in excellent dispersion of Pt along both inner and outer walls. Structural and morphological characterizations using high resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD) revealed that when Pt could be dispersed along the inner as well as the Outer walls of CNF, the Pt particle size decreased to almost half as compared to the one With Pt decoration only along a single wall of the Substrate material. Further, electrochemical studies using cyclic voltammetry (CV) and rotating disk electrode (RDE) measurements revealed enhanced methanol oxidation and oxygen reduction properties, respectively. The electrochemical active area obtained for the catalyst with both inner and outer wall Pt decoration wits nearly two times higher than that corresponding to the one with only inner wall Pt decoration. Similarly, the rate constant for the oxygen reduction reaction displayed by this sample was four times higher in comparison with the sample prepared by Utilizing only one wall for Pt decoration.

High aspect ratio nanoscale multifunctional materials derived from hollow carbon nanofiber by polymer insertion and metal decoration - Balan, Beena K.; Kale, Vinayak S.; Aher, Pradnya P.; Shelke, Manjusha V.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2010)
A novel high aspect ratio material which can simultaneously display multiple functions such as proton and electron conductivity and electrocatalytic activity has been developed by incorporating both platinum nanoparticles and phosphoric acid doped polybenzimidazole along the inner and outer surfaces of a hollow carbon nanofiber.

Enhanced electrocatalytic performance of interconnected Rh nano-chains towards formic acid oxidation - Sathe, Bhaskar R.; Balan, Beena K.; Pillai, Vijayamohanan K. (Energy & Environmental Science, 2011)
A chain-like assembly of rhodium nanoparticles (5-7 nm mean diameter) has been synthesized from rhodium chloride with the help of polydentate molecules like tartaric and ascorbic acids (1 : 3 in mM scale) as capping agents at room temperature. Subsequent characterization using transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy reveals a unique inter-connected network like features, while their electrochemical behavior using cyclic voltammetry and current-time transient suggests potential applications as electrocatalysts in fuel cells. A significant negative shift in the onset potential as well as higher anodic peak current density for formic acid oxidation on Rh-tartaric acid (Rh-TA) as compared to that of bulk Rh metal confirms their higher electrocatalytic activity. Interestingly, the enhancement factor (R) with respect to that of bulk metallic Rh towards formic acid oxidation ranges up to 2000% for Rh-TA and 1200% for Rh-AA (Rh-ascorbic acid) respectively. The composition of Rh nano-chains has been further analyzed with thermogravimetry and Fourier transform infra-red spectroscopy to demonstrate the importance of controlling the chain topology using polyfunctional organic molecules. These findings open up new possibilities for tailoring nanostructured electrodes with potential benefits since the development of a better electrocatalysts for many fuel cell reactions continues to be an important challenge.

Highly exposed and activity modulated sandwich type Pt thin layer catalyst with enhanced utilization - Balan, Beena K.; Kurungot, Sreekumar (Journal of Materials Chemistry, 2011)
A Pt thin layer catalyst supported on an in situ prepared `RuO(2)-carbon-RuO(2)' sandwich type hybrid support is presented. This is achieved by the extensive functionalization of a hollow carbon nanofiber support to introduce oxygen containing functional groups (FCNF) with the specific aim to accomplish the exclusive adsorption of Ru ions along its inner cavity and outer surfaces. Preferential adsorption of Ru ions from a mixture of Pt and Ru with sufficient time for adsorption and reorganization of ions on the carbon nanofiber surface leads to the in situ renovation of FCNFs to form a hybrid `RuO(2)-carbon-RuO(2)' sandwich type support followed by Pt nanoparticle decoration. While the selective exposure of Pt on the hybrid support surface is confirmed from the HRTEM analysis, the electronic changes effected in the CNF support are evident from the XPS and XRD analysis. Finally, the potential benefit of such a design is also demonstrated using electrochemical studies, where the three-fold increase in the electrochemically active surface area from cyclic voltammetric analysis, a four-fold improvement in the limiting current density coupled with a 80 mV gain in onset potential from rotating disc electrode studies for the oxygen reduction reaction, and a drastic reduction in the CO poisoning for methanol oxidation reaction underlines the superb performance of this material. Such an exceptionally high performance can be attributed to the strong electronic perturbations occurring in the Pt and the FCNF support due to the presence of a continuous RuO(2) layer in between. Such a high aspect ratio core-shell type design with an unusual enhancement in the Pt utilization establishes the roles of both the hybrid support and active catalyst to address the future challenges in the area of utilization improvement.

One-dimensional confinement of a nanosized metal organic framework in carbon nanofibers for improved gas adsorption - Pachfule, Pradip; Balan, Beena K.; Kurungot, Sreekumar; Banerjee, Rahul (Chemical Communications, 2012)
The loading of a Zn-terephthalate based MOF in the inner cavity as well as on the outer walls of a hollow carbon nanofiber (CNF) creates MOF@CNF hybrids. This hybrid ``MOF@CNF'' displayed improved thermal stability as well as gas adsorption compared to the individual counterparts.

Polybenzimidazole mediated N-doping along the inner and outer surfaces of a carbon nanofiber and its oxygen reduction properties - Balan, Beena K.; Manissery, Aiswarya Padinhare; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
Nitrogen-doped (N-doped) hollow carbon nanofiber (CNF) was synthesized by incorporating a nitrogen containing polymer precursor, polybenzimidazole (PBI-BuI), in the inner cavity as well as on the outer walls of the CNF, followed by a high temperature treatment. PBI-BuI incorporation along the inner and outer surface of the CNF was accomplished by synthesizing a low molecular weight polymer by tuning the synthetic parameters. The solution concentration of the PBI-BuI is also varied to facilitate its entry into the CNF by capillary action. The high temperature treatment (700-1000 degrees C) of the resulting CNF-PBI material decomposes the polymer and induces N-doping along the inner and outer surfaces of the CNF. The initial PBI-BuI content and the annealing temperature are also systematically varied to choose the right combination of starting precursors and heat-treatment conditions. Detailed X-ray photoelectron spectroscopy analysis of the samples shows that pyridinic-type nitrogen is the major component in all the samples. Electrochemical characterizations of this material using cyclic voltammetry, rotating disc electrode studies and durability analysis demonstrated that this material can act as a metal-free oxygen reduction electrocatalyst with improved oxygen reduction kinetics and stability. It is also revealed that the onset potential, limiting current density, number of transferred electrons, etc. have a strong dependence on the annealing temperature.

Significant enhancement of formic acid oxidation using rhodium nanostructures - Balan, Beena K.; Sathe, Bhaskar R. (Journal of Nanoscience and Nanotechnology, 2012)
The electrocatalytic activity of as-synthesized shape selective Rh nanostructures has been demonstrated using cyclic voltammetry, revealing unique shape-dependant performance towards HCOOH oxidation. interestingly, the enhancement factor (R) for different shapes of Rh with respect to that of commercial Rh towards formic acid oxidation ranges up to 20,000% for cubes as compared to 17,500% for pyramids and 11,000% for hexagons respectively. Mechanistic pathway for comparatively better sensitivity of cubes as compared to other shapes has been correlated with the results of X-ray diffraction.
Keywords: electrocatalysis; Formic Acid Oxidation; Preferential Growth; Rhodium Nanostructures

Tuning the functionality of a carbon nanofiber-Pt-RuO2 system from charge storage to electrocatalysis - Balan, Beena K.; Kurungot, Sreekumar (Inorganic Chemistry, 2012)
Chemical-functionalization-induced switching in the property of a hybrid system composed of a hollow carbon nanofiber (CNF) and Pt and RuO2 nanoparticles from charge storage to electrocatalysis is presented. The results of this study show how important it is to have a clear understanding of the nature of surface functionalities in the processes involving dispersion of more than one component on various substrates including carbon nanomorphologies. When pristine CNF is used to decorate Pt and RuO2 nanoparticles, random dispersion occurs on the CNF surface (C-PtRuO2). This results in mainly phase-separated nanoparticles rich in RuO2 characteristics. In contrast to this, upon moving from the pristine CNF to those activated by a simple H2O2 treatment to create oxygen-containing surface functional groups, a material rich in Pt features on the surface is obtained (F-PtRuO2). This is achieved because of the preferential adsorption of RuO2 by the functionalized surface of CNF. A better affinity of the oxygen-containing functional groups on CNF toward RuO2 mobilizes relatively faster adsorption of this moiety, leading to a well-controlled segregation of Pt nanoparticles toward the surface. Further reorganization of Pt nanoparticles leads to the formation of a Pt nanosheet structure on the surface. The electrochemical properties of these materials are initially evaluated using cyclic voltammetric analysis. The cyclic voltammetric results indicate that C-PtRuO2 shows a charge storage property, a typical characteristic of hydrous RuO2, whereas F-PtRuO2 shows an oxygen reduction property, which is the characteristic feature of Pt. This clear switch in the behavior from charge storage to electrocatalysis is further confirmed by galvanostatic charge discharge and rotating-disk-electrode studies.

Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrids for improved supercapacitor performance - Balan, Beena K.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (RSC Advances, 2013)
Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrid electrode material which integrates dual wall decoration and interfacial area tuning for supercapacitor applications has been devised based on a simple approach. This is achieved by decorating RuO2 nanoparticles of size ca. 2-3 nm along the inner and outer walls of a hollow carbon nanofiber (CNF) support (F-20RuO(2)). In the next step, a proton conducting polymer, phosphoric acid doped polybenzimidazole (PBI-BuI), interface is created along the inner and outer surfaces of this material. A 103% increase in the specific capacitance is obtained for RuO2-PBI hybrid material as compared to that of F-20RuO(2) at the optimum level of the polymer wrapping. Apart from the high specific capacitance, the RuO2-PBI hybrid materials exhibit enhanced rate capability and excellent electrochemical stability of 98% retention in the capacitance. Such a remarkably high activity can be primarily attributed to the efficient dispersion of active sites achieved by properly utilizing inner and outer surfaces of CNF. Apart from this, the facile routes for ion transport created as a result of PBI incorporation coupled with excellent interfacial contact between the RuO2 and the electrolyte resulting in the improved utilization of the active material also contribute to the improved activity. In addition to this, the synergistic effects of pseudocapacitive contribution from both the PBI-BuI and RuO2 also contribute to the redefined performance characteristics.

Effect of the viscosity of poly(benzimidazole) on the performance of a multifunctional electrocatalyst with an ideal interfacial structure - Balan, Beena K.; Unni, Bipinlal; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2013)
A novel electrocatalyst system with unique multifunctional characteristics, originated by the presence of a proton conducting polybenzimidazole (PBI-BuI) bound layer and electron conducting hollow carbon nanofibers (CNF) with catalytically active Pt nanoparticles, has been devised based on a simple strategy. This was achieved by decorating Pt nanoparticles along the inner cavity, as well as on the outer walls of the hollow CNF support (F-Pt). In a further extension, a low molecular weight PBI, synthesized by optimizing the experimental parameters, was incorporated into the inner cavity and along the outer surfaces of F-Pt. Excellent dispersion of the Pt nanoparticles was achieved by properly utilizing the available carbon surface results in improved electrocatalytic activity, while the CNF backbone ensures high electron conductivity as well. The polymer binder coverage formed along the inner and outer wall surfaces provides an efficient triple phase boundary (TPB) around the Pt nanoparticles to facilitate the electrode reactions. The amount and the viscosity of the PBI-BuI in the electrode material were systematically varied to study the influence on the electrochemical performance. Transmission electron microscopy analysis confirms PBI insertion into the tubular cavity of CNF. Pore size distribution analysis implies that both the viscosity and the amount of PBI-BuI have a pivotal role in defining the microstructure of the electrode. Electrochemical studies using cyclic voltammetry (CV) and rotating disc electrode (RDE) reveal the exceptionally high activity of this hybrid material with an improved electrochemically active area. The significant improvement for the oxygen reduction reaction is further confirmed by the single cell analysis also. The high power density displayed by the PBI-BuI based system, as compared to the Nafion based system, validates the conceptualization of the well controlled triple-phase boundary in the system. These results demonstrate that PBI-BuI has a constructive effect in tuning the electrochemical activity at an optimum amount and at a favourable viscosity of the proton conducting polymer.